Ketidakadilan Gender Dalam Novel Tarian Bumi Karya Oka Rusmini : Tinjauan Sastra Feminis Dan Implementasinya Dalam Pembelajaran Sastra Di SMA - Setianingrum, Nur Asih (2016)
This research has 4 goals. 1) To describe the sosiohistoris background of Oka Rusmini as an author of "Tarian Bumi" novel. 2) To describe the structural study of "Tarian Bumi " novel by Oka Rusmini . 3) To describe gender inequalities in Oka Rusmini's novel "Tarian Bumi" based on literary criticism feminism. 4) To describe the implementation of perspective gender in Oka Rusmini's novel "Tarian Bumi" as Indonesian literature material in SMA.This type of research was qualitative descriptive. The object of this research was perspective gender in Oka Rusmini's novel "Tarian Bumi". The subject of this research was "Tarian Bumi" novel by Oka Rusmini. The techniques of data collection in this study used a library technique and record. Triangulation that used in this research was data triangulation and triangulation theory. The result of this research show that:1) Sosiohistories of Oka rusmini very interesting. Oka Rusmini is ones of the women novelist that bring feminist in the theme of her novel.Oka Rusmini was`born in Jakarta, the 11th of July in 1967. She always write the gender in her novels. 2) Structurally the theme of "Tarian Bumi" novel by Oka Rusmini was about a woman who wanted the equality with men. The storyline that was used by Oka Rusmini was Flash-back plot. The characterizations were divided into two.Key figures and additional figures. In this novel, the key figures were "Ida Ayu Telaga Pidada" as a protagonist figure.As an antagonist figure is Luh Sekar. The additional figures were Wayan Sasmitha, Ida Bagus Tugur, Luh Gumbreg, Luh Kenten. The scene background all took a place in Bali. The time background happened in the morning and in the night. The social background was in situation of the patrikiart era. 3)Inequalities gender in "Tarian Bumi" novel by Oka Rusmini has inequalities gender included 5 things. (a) Women marginilitation. (b) Women subordinatition. (c) Women stereotype. (d) Women violence. (e) Women workload. 4) Implications of education elements contained in the novel "Tarian Bumi" by Oka Rusmini as a learning material in SMA could be seen from the relevance to the aims of education,hhe relevance to the content standards, the relevance to learners.